2021
DOI: 10.1371/journal.pone.0255692
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the sex-specific differences in the association of smoking on the survival rate of hospitalized COVID-19 patients

Abstract: Introduction In the absence of a universally accepted association between smoking and COVID-19 health outcomes, we investigated this relationship in a representative cohort from one of the world’s highest tobacco consuming regions. This is the first report from the Middle East and North Africa that tackles specifically the association of smoking and COVID-19 mortality while demonstrating a novel sex-discrepancy in the survival rates among patients. Methods Clinical data for 743 hospitalized COVID-19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In our sample, smoking prevalence was 57.8% exceeding the WHO prevalence estimates of current tobacco smoking in 2018 (42.6%) [ 31 ], as well as the prevalence of tobacco smoking reported among the hospitalized COVID-19 patients of Khalil et al study (42.3%) [ 33 ]. Results also revealed a high prevalence of tobacco smoking among male participants (58.2%) compared to their females counterparts (41.8%) which also exceeded the WHO prevalence estimates of current tobacco (49.2% and 35.9% males and females respectively) [ 31 ].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In our sample, smoking prevalence was 57.8% exceeding the WHO prevalence estimates of current tobacco smoking in 2018 (42.6%) [ 31 ], as well as the prevalence of tobacco smoking reported among the hospitalized COVID-19 patients of Khalil et al study (42.3%) [ 33 ]. Results also revealed a high prevalence of tobacco smoking among male participants (58.2%) compared to their females counterparts (41.8%) which also exceeded the WHO prevalence estimates of current tobacco (49.2% and 35.9% males and females respectively) [ 31 ].…”
Section: Discussionmentioning
confidence: 51%
“…This results was consistent with other studies [ 15 , 16 ]. However, upon stratifying the sample by gender, multinomial logistic regression models revealed a significant association among male with mild infection compared to their asymptomatic counterparts (OR = 1.78, 95% CI (1.01–3.13)), a recent study conducted in Lebanon among 743 hospitalized COVID-19 patients revealed a high smoking prevalence (42.3%) combined with worse prognosis as well as a higher mortality rate in smoking patients [ 33 ]. A gender-discrepancy in the association of smoking on COVID-19 mortality rates was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Current smoking status was associated with more complications, but it was not associated with heath recovery and return to the usual health. In some studies, current smoking is a risk factor of illness severity, but there are different results with respect to complications [56,59,[73][74][75][76]. However, the incidence of COVID-19 in current smokers is lower than in non-smokers [77].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that COVID-19 primarily targets the lungs; smokingrelated lung disorders often overlap with other respiratory comorbidities in COVID-19 patients, such as chronic bronchitis, chronic obstructive pulmonary disease, and emphysema (Alluhaymid et al, 2020). However, research remains on smoking as a risk factor for a worse COVID-19 prognosis and calls for quitting smoking amid the pandemic (Khalil et al, 2021). The results showed that the female sex had a longer hospitalization length than the male.…”
Section: Smokementioning
confidence: 99%
“…12 (Khalil et al, 2021) A Retrospective study 743 patients at Rafik Hariri University Hospital (RHUH)…”
Section: (Al-salameh Et Al 2021)mentioning
confidence: 99%